Evaluasi Pendidikan Karakter Disiplin Siswa di Sekolah Dasar - Cahyaningtyas, Arifah Yuni; Fatmasari, Erna Dwi; Annisa, Iut Diyah; Irta, Aisha; Ainur, Asri (Nur Science Institute, 2023)
Background: Planting character education in schools is carried out through daily activities in the school environment. One of them is the character value of discipline. The purposes of this study: 1) evaluate the achievement of the character education program at the elementary school level in Sukoharjo Regency, 2) provide input and suggestions to teachers and schools for improving the character program. Method: This type of research is program evaluation with a quantitative approach. The subjects of this study included: 5th grade students, homeroom teachers, teachers, security guards and parties directly related to students in carrying out activities at school related to character education. This study used interview, questionnaire, and observation techniques. Result: The conclusions from this study are: 1) the disciplinary character education program at SD Negeri 2 Gonilan is running well or it can be said to be successful, 2) the suggestions and input that we give to schools are that schools can provide outreach to the community regarding the importance of disciplinary character education and how to apply it at home so that students can apply the character of discipline at school and at home so that it is not only carried out in learning, but also outside of learning in daily activities in the school environment. Implication: The implications of this study are: First, the elementary schools' headmasters in Indonesia should enrich the teachers' knowledge and insight related to character education assessment. Second, the government, supported by researchers, has to design an excellent assessment system to solve time limitations. Novelty: The present study revealed the implementation of character education in elementary school comprehensively.